Low-temperature sonoelectrochemical processes Part 1. Mass transport and cavitation effects of 20 kHz ultrasound in liquid ammonia - Del Campo, F; Neudeck, A; Compton, R; Marken, F (Elsevier, 1999)
Sonoelectrochemical processes in liquid ammonia in a temperature range between -70 and -35 °C in the presence of 20 kHz power ultrasound are studied with the aim of improving low temperature electrosynthetic procedures. The one and two electron reductions of nitrobenzene and para-chloronitrobenzene are investigated as model systems. Placing an immersed ultrasonic horn emitter `face-on' to a platinum disc electrode in liquid ammonia is shown to result in extreme mass transport enhancements with a resulting diffusion layer thickness of approximately δ = 2 μm. This limit of the diffusion layer thickness is shown to be essentially temperature independent and correspondingly, the highest limiting currents can be observed near the boiling point of liquid ammonia. Cavitation processes are detected even at -70 °C and result in a considerable fluctuation in the observed mass transport controlled limiting current. Further, the deposition of ionic products formed in the second reduction step for both nitrobenzene and para-chloronitrobenzene reduction and the associated drop in current, can be shown to be affected by sonication. Ultrasound has been found to be beneficial by (i) causing extremely fast mass transport; (ii) enhancing the mixing and dissolution kinetics at low temperature; and (iii) affecting the formation of solid products at the electrode surface.